Contribution of Aachen High Shear Reactor & Filblast Low Shear Reactor as Gold Ore Pre-Treatment Leaching at Geoservices (Ltd.) - Keyhadi Billah Al Wafi; Yasmina Amalia (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Gold (Au) as a precious metal has played significant role throughout human history. Most gold ores subjected to leaching using the sodium cyanide (NaCN) contain high levels of base metals. High base metal content can influence the recovery of pregnant leach solution (PLS), as it affects the consumption of sodium cyanide (NaCN) and lime used to optimize the gold ore leaching process. Pre treatment leaching process is required for gold ores before the leaching process is carried out. In this study, a pre treatment leaching process was carried out using the Aachen High Shear and Filblast Low Shear Reactors with variations in feed solids percentage for each reactor, utilizing NaCN concentrations of 1000 ppm for the Aachen with bottle roll test (BRT) and 500 ppm for the Filblast with agitations leach test (ALT). Based on this study, each pre-treatment leaching reactor, the extraction percentages were 54.30% Au, 63,40% Ag for the Aachen and 52.19% Au and 68,10% Ag at Filblast. Lime consumption in the Aachen was highest at 3.47 kg/t (PreOx 3 and AAL), while in Filblast at 1.71 kg/t. Meanwhile, NaCN consumption in the Aachen was highest at 0.64 kg/t (PreOx 2), compared to 0.80 kg/t in Filblast.